ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELUARAN KONSUMSI RUMAH TANGGA PADA PENERIMA BANTUAN LANGSUNG TUNAI (BLT) (Studi pada Gampong Lamreung Kecamatan Darul Imarah Kabupaten Aceh Besar) - Yulindawati Linda; Isthafan Najmi; Reza Maulana (Faculty of Islamic Economics and Business at Universitas Islam Negeri Ar-Raniry in Banda Aceh, Indonesia, 2023)
One of the government programs to reduce poverty and improve people's welfare is to provide Direct Cash Assistance (BLT). So therefore the level of welfare in a society can be said to improve if part of the income is used to consume food and non-food. This study aims to examine and analyze income, number of family members, and savings on household consumption expenditure for recipients of direct cash assistance (BLT) in Gampong Lamreung, Darul Imarah Aceh Besar district. The population in this study were BLT beneficiary communities who were registered as beneficiary families in Lamreung Village, Darul Imarah District. The sample taken in this study is a full sample, which means using the entire population as respondents, therefore the sample in this study is 60 respondents. This study uses a quantitative approach using primary data or so-called field research (Fild Research). Data collection techniques using questionnaires / questionnaires. The research method used is the Multiple Linear Regression Analysis method. Based on the results of the coefficient of determination, it can be seen that the R2 value is 0.354. Which means that the ability of the independent variable to explain the dependent variable is 35.4%, the remaining 64.6% can be explained by other variables not explained in this study.